A new generation of aprotic yet Bronsted acidic imidazolium salts: low toxicity, high recyclability and greatly improved activity - CONNON, STEPHEN (My University, 2013)
Catalysts which have low antimicrobial toxicity and are aprotic, yet which can act as Brønsted acidic catalysts in the presence of protic additives have been developed. The catalysts are recyclable, considerably more active (i.e. can be used at 10–50 times lower loadings) and of broader scope than their antecedent generation.
PUBLISHED
Keywords: Brønsted acidic catalysts